Cash Flow Statement Analysis to Determine the Level of Liquidity at PT. Astra Agro Lestari Tbk Period 2021-2023 - Elisa Cici Prisilia; Elisabet Lumban Gaol; Riskana Natalia Br Bangun; Dwi Saraswati (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The purpose of this study is to determine the level of liquidity of PT. Astra Agro Lestari Tbk using cash flow statement analysis. The population of this study is the annual financial statements of PT. Astra Agro Lestari Tbk from 2021 to 2023. The example used in this study is the cash flow statement from 2021 to 2023. The results of the study show that changes in the three-year cash flow statement affect the company's cash flow position. In 2023, the company's operating activities increased, but in 2021–2022 they fell to a negative value. In 2023, the company's operating activities only increased, but were still negative. In 2021–2023, investment activities also decreased in value due to a decrease in loans for the purchase of fixed assets, expansion of production facilities, and expansion of biological assets. In addition, fundraising activities continued to decline, with the largest decline occurring between 2021 and 2023. The company has been illiquid for the past three years, according to its liquidity measurement with its cash ratio. Due to the inability to provide cash and cash equivalents, current liabilities then increased. The current industry standard is well below the cash ratio. This value will exceed the industry standard for the first time in 2022, indicating that the company is able to pay its short-term debt this year.